Representation of Power Relations in English: a Cognitive Approach - Liudmila A. Furs; Irina V. Kolomlina (RUDN Journal of Language Studies, Semiotics and Semantics)
The representation of power relations in English from the perspective of a cognitive approach made it possible to reveal the specifics of this complex phenomenon by establishing its conceptual basis, defining the conceptual areas in which power relations are realized, and describing the methods of their representation. Based on the conceptual and definitional analysis of lexemes of the same name, such characteristics of the POWER concept as “control”, “strength”, “influence” were determined. As a result of cognitive modeling, a hierarchical structure of the POWER RELATIONS frame is presented, in which the obligatory components are “subject”, “act of power relations”, “object” and “method”, and the optional components are “source of power”, “tool” and “goal”. A model of power relations has also been developed in relation to the ways of their implementation in English. It has been determined that power relations are implemented in the conceptual areas of STATE, CORPORATE RELATIONS and INTERPERSONAL RELATIONS. The presented model reflects the variability of ways of implementing power relations in different conceptual areas and demonstrates the specificity of their representation in relation to the nature of the relationship between the subject and the object of power relations. Understanding of power relations is based on two types of categorization - primary, when the profiling mechanism is activated, and secondary (evaluative), based on the mechanisms of conceptual metonymy, metaphor and metaphtonymy. This aspect also indicates that in the processes of representing power relations, two types of knowledge are involved - declarative and procedural, which is typical for phenomena of a complex nature. The prospect of the study is the possibility of using the developed methodology in the analysis of other complex phenomena.